Remote Sensing and GIS for Groundwater Potential Zones Ghagger Watershed, Himachal Pradesh - Singh, Lakhwinder; Khare, Deepak; Mishra, Nitin (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*339.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942416);" role="presentation">Groundwater is often referred to as the ‘hidden’ component of the hydrological cycle because it is not directly <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*352.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944253);" role="presentation">observable. However, in many areas, the groundwater resource is huge, and its occurrence and hydrological <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*366.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94395);" role="presentation">significance cannot be negl<span dir="ltr" style="left: calc(var(–scale-factor)*185.54px); top: calc(var(–scale-factor)*366.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953615);" role="presentation">ected in water management and planning. Identification of groundwater potential <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926131);" role="presentation">zone is main objective of present work for Ghagger Watershed<span dir="ltr" style="left: calc(var(–scale-factor)*327.31px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909478);" role="presentation">, Himachal Pradesh. GIS and Remote Sensing is <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.978616);" role="presentation">used for identification of groundwater potential zones in the study ar<span dir="ltr" style="left: calc(var(–scale-factor)*364.51px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964877);" role="presentation">ea. Landsat 8 satellite data is used to <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*405.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89961);" role="presentation">generate land use and land cover maps as well as your Geomorphological maps for the study area. Soil maps are <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*419.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.969224);" role="presentation">used as available. Digital elevation model are acquired using CartoSAT-<span dir="ltr" style="left: calc(var(–scale-factor)*379.27px); top: calc(var(–scale-factor)*419.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.972076);" role="presentation">1 satellite Data. Weighted overlay <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*432.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938896);" role="presentation">method of raster dataset for analysis is used to identify groundwater potential zone of study area. <span dir="ltr" style="left: calc(var(–scale-factor)*479.87px); top: calc(var(–scale-factor)*432.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921461);" role="presentation">The layers <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*445.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938912);" role="presentation">landuse, Elevation, slope, geomorphology, rainfall pattern, drainage pattern and soil were considered and the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*458.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928551);" role="presentation">influence <span dir="ltr" style="left: calc(var(–scale-factor)*112.22px); top: calc(var(–scale-factor)*458.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899978);" role="presentation">and scale values set to <span dir="ltr" style="left: calc(var(–scale-factor)*206.69px); top: calc(var(–scale-factor)*458.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944389);" role="presentation">different feature <span dir="ltr" style="left: calc(var(–scale-factor)*274.85px); top: calc(var(–scale-factor)*458.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925582);" role="presentation">according to their importance in groundwater potential areas. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*471.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924001);" role="presentation">After analysis, five zones of groundwater potential are generated as, very poor, poor, moderate, Good and very <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*485.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934993);" role="presentation">good were identified for the study area. It estimated is for stu<span dir="ltr" style="left: calc(var(–scale-factor)*321.91px); top: calc(var(–scale-factor)*485.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912224);" role="presentation">dy area that 49% and 29% part is lies in moderate <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*498.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912653);" role="presentation">to good zone of groundwater